Human Capital, Product Quality, and Growth - Stokey, Nancy L. (Quarterly Journal of Economics, 1991)
A model of growth is developed in which finite-lived individuals invest in human capital, investments have a positive external effect on the human capital of later cohorts, and labor with more human capital produces higher-quality goods. Stationary growth paths are analyzed, paths along which human capital and the quality of goods grow at a common, constant rate. It is also shown that if a small open economy is either very advanced or very backward relative to the rest of the world, then its rate of investment in human capital is lower under free trade than under autarky.